Influence of Light Availability and Prey Type on the Growth and Photo-Physiological Rates of the Mixotroph Noctiluca scintillans - Gomes, Helga do Rosario; McKee, Kali; Mile, Anxhela; Thandapu, Sharanya; Al-Hashmi, Khalid; Jiang, Xiaojian; Goes, Joaquim I. (Frontiers in Marine Science, 2018)
A strain of the mixotrophic green Noctiluca scintillans (Noctiluca) isolated from the Arabian Sea afforded us an opportunity to investigate the photosynthetic and feeding characteristics of this organism which has recently replaced the once diatom dominated food chain of winter blooms in the Arabian Sea. Here we present the first in a series of experiments undertaken to study the interactive effects of irradiance and grazing response of this mixotroph to four phytoplankton species provided as food. Noctiluca showed a distinct preference for the dinoflagellate Peridinium foliciaeum and the diatom Phaeodactylum tricornutum but not the chlorophyte Pyramimonas nor the chain forming diatom Thalassiosira weissflogii. However, irrespective of food provided, adequate light was required for Noctiluca to grow as evidenced by its maximum growth rates of 1.44 cells day-1 when fed the preferred Peridinium and exposed to optimal irradiance of 250 E m-2 s-1 versus growth rates of 0.18 cells day-1 with the same food but at a low irradiance of 10 E m-2 s-1. Measurements of Noctiluca’s electron transport rates (ETR) per PSII Reaction Center as a function of irradiance also indicated severe light limitation of photosynthesis at 10 E m-2 s-1. The active fluorescence derived ETR versus Irradiance curves revealed an interesting finding in that there was no significant difference in photosynthetic parameters such the maximum photosynthetic capacity (ETRmax) nor α, the rate of increase of photosynthesis with light between fed and unfed cells under optimal light conditions. These results suggest that feeding does not enhance the photosynthetic activity of the endosymbionts when nutrients are not limiting as was the case in these experiments. Measurements of Noctiluca’s intracellular ammonium concentrations under optimal light conditions, the first for this strain, show significant accumulation of NH4+ (0.003-0.012 M NH4+ cell-1) after 14 days for fed and unfed Noctiluca which was undetectable 4 days later. A similar 14-day increase but of significantly higher concentrations (0.005-0.08 M NH4+ cell-1) was obtained under low light conditions. For Phaeodactylum and Thalassiosira fed cultures under light limitation, NH4+ continued to increase past the 14-day period suggesting Noctiluca's strong and efficient mechanism for regulation of intracellular nutrients.